Arctic seals as tracers of environmental and ecological change. Issue 1 (12th November 2020) - de la Vega, Camille; Mahaffey, Claire; Tuerena, Robyn E.; Yurkowski, David J.; Ferguson, Steven H.; Stenson, Garry B.; Nordøy, Erling S.; Haug, Tore; Biuw, Martin; Smout, Sophie; Hopkins, Jo; Tagliabue, Alessandro; et al.
Abstract: Knowledge of species trophic position (TP) is an essential component of ecosystem management. Determining TP from stable nitrogen isotopes (δ 15 N) in predators requires understanding how these tracers vary across environments and how they relate to predator isotope composition. We used two seal species as a model for determining TP across large spatial scales in the Arctic. δ 15 N in seawater nitrate (δ 15 NNO3 ) and seal muscle amino acids (δ 15 NAA ) were determined to independently characterize the base of the food web and the TP of harp and ringed seals, demonstrating a direct link between δ 15 NNO3 and δ 15 NAA . Our results show that the spatial variation in δ 15 NAA in seals reflects the δ 15 NNO3 end members in Pacific vs. Atlantic waters. This study provides a reference for best practice on accurate comparison of TP in predators and as such, provides a framework to assess the impact of environmental and human‐induced changes on ecosystems at pan‐Arctic scales.